Sexual transmission of murine papillomavirus (MmuPV1) in Mus musculus - Megan E Spurgeon; Paul F Lambert (eLife, 2019)
Human papillomaviruses (HPVs) are the most common sexually transmitted infectious agents. Because of the species specificity of HPVs, study of their natural transmission in laboratory animals is not possible. The papillomavirus, MmuPV1, which infects laboratory mice (Mus musculus), can cause infections in the female cervicovaginal epithelium of immunocompetent mice that progress to cancer. Here, we provide evidence that MmuPV1 is sexually transmitted in unmanipulated, immunocompetent male and female mice. Female 'donor' mice experimentally infected with MmuPV1 in their lower reproductive tract were housed with unmanipulated male mice. The male mice were then transferred to cages holding 'recipient' female mice. One third of the female recipient mice acquired cervicovaginal infections. Prolonged infections were verified by histopathology and in situ hybridization analyses of both male and recipient female mice at the study endpoint. These findings indicate that MmuPV1 is a new model animal papillomavirus with which to study sexually transmission of papillomaviruses.